Psychiatric patients' return for HIV/STI test results in mental health centers - Ana Paula Souto Melo; Karen McKinnon; Milton L Wainberg; Cibele Comini César; Mark Drew Crosland Guimarães (Universidade de São Paulo, 2012)
OBJECTIVE: To assess individual and/or health service factors associated with patients returning for results of HIV or sexually transmitted infection (STI) tests in mental health centers. METHODS: Cross-sectional national multicenter study among 2,080 patients randomly selected from 26 Brazilian mental health centers in 2007. Multilevel logistic regression was used to assess the effect of individual (level 1) and mental health service characteristics (level 2) on receipt of test results. RESULTS: The rate of returning HIV/STI test results was 79.6%. Among health service characteristics examined, only condom distribution was associated with receiving HIV/STI test results, whereas several individual characteristics were independently associated including living in the same city where treatment centers are; being single; not having heard of AIDS; and not having been previously HIV tested. CONCLUSIONS: It is urgent to expand HIV/STI testing in health services which provide care for patients with potentially increased vulnerability to these conditions, and to promote better integration between mental health and health services.